Um novo método criptográfico baseado no cálculo de pré-imagens de autômatos celulares caóticos, não-homogêneos e não-aditivos - Macêdo, Heverton Barros de (2007)
A new cryptographic method based on cellular automata (CA) has been investigated. In this method, the ciphering process is performed by preimages computation while deciphering is performed by CA temporal evolution. The preimages calculus is able to be used in a cryptographic system only if any arbitrary CA lattice has at least one preimage. In a previous method proposed by Gutowitz, this guarantee of pre-image was obtained due to the toggle property of the rules used as keys and some additional bits used in the calculus. Here a new method is proposed in which two distinct types of toggle rules are used without the need of additional bits. As a consequence, the cipher text and the plain text have the same size. One of the rules has the toggle property and it is responsible for CA dynamical behavior. The other rule is responsible to guarantee preimage existence, without need of additional bits. This method also differs from other cryptographic models based on additive rules previously published. The model is resistant against an attack known as differential cryptanalysis. Besides, it is efficient considering hardware implementation due to the intrinsic parallelism of the model.